Becoming Hispanic-Serving Institutions : Opportunities for Colleges and Universities - Garcia, Gina Ann, 1978- (Book collections on Project MUSE., 2019)
"Hispanic-Serving Institutions (HSIs)--not-for-profit, degree-granting colleges and universities that enroll at least 25 percent or more Latinx students--are among the fastest-growing segments in America. They now represent 13 percent of all postsecondary institutions in the United States and enroll 62 percent of all Latinx college students. As they increase in number, the question remains: What does it mean to serve Latinx students? What special needs does this student demographic have? What opportunities develop when a college or university becomes an HSI? Using multiple case studies, Gina Ann Garcia explores how institutions are developing ways to serve Latinx students and how those institutions confront the tensions that emerge from confronting traditional standards for postsecondary institutions, which include indicators of prestige, selectivity, graduation rates, and federal research dollars"--